Relevansi Pemikiran Imam Syafi’i Tentang Mafqud Terhadap Perceraian Ghaib: (Studi Kasus di Pengadilan Agama Jombang) - Dimyati, Yayat (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2024)
In the mind of Imam Shafi'i there are those who argue that if the husband or wife who mafqud must wait for four years. and according to the Law and Compilation of Islamic Law is to wait with a period of 2 years. The period between these two opinions is very long if compared. This is because the sophisticated transportation and information systems present in the modern era provide a quick opportunity to find out the existence of the mafqud. Unlike the past who still do not know the transportation and information system. So here see which is more relevant to follow between the thoughts of Imam Shafi'i or the Law and Compilation of Islamic Law. In this thesis examines the Relevance of Imam Shafi'i's Thoughts on Mafqud Against Divorce Ghaib Case Study in Jombang Religious Court. This research aims to find out the opinion of Imam Shafi'i about mafqud and the ruling of the Jombang Religious Court regarding mafqud divorce. In this study, the authors used descriptive research methods that seek to describe and analyze problems in as much detail as possible. The type of research used is library research by tracing theories contained in libraries and fields. The results showed that there is no one proposition of the Qur'an and hadith that mentions the deadline for the determination of the time of missing persons, which there is only the opinion of a friend, Umar bin Al-Khatab. But Umar's opinion was only for wives who lost husbands. In addition, it can also be known the consequences of mafqud that can occur to people around or his heirs and he becomes a demand to solve it. Based on the study of the authors conducted, in this study it can be concluded that the Author hopes that ijtihad is carried out by mujtahids at any time such as judges. Because the law is dynamic will change over time following the changing era of times.